1985
DOI: 10.1007/bf02620918
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fibronectin-related peptides on cell spreading

Abstract: Four synthetic peptides related in amino acid sequence to the area of the fibronectin molecule thought to be involved in cell binding were tested for the ability to inhibit cell spreading promoted by several different attachment factors. Effects of the peptides were assayed on a number of cell types. For all cell types tested, peptides effective at inhibiting fibronectin-promoted cell spreading were found also to inhibit cell spreading promoted by human serum spreading factor (SF). These peptides were also cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…Peptides containing the sequence Arg-Gly-Asp-Ser (RGDS), originally identified in the cell-binding domain of fibronectin, have been shown to be competitive, reversible inhibitors of cellular adhesion to extracellular matrix components (6)(7)(8). A relatively strict requirement for the particular sequence ofamino acids in these peptides has been established as a result of extensive analysis in vitro (6,7,9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Peptides containing the sequence Arg-Gly-Asp-Ser (RGDS), originally identified in the cell-binding domain of fibronectin, have been shown to be competitive, reversible inhibitors of cellular adhesion to extracellular matrix components (6)(7)(8). A relatively strict requirement for the particular sequence ofamino acids in these peptides has been established as a result of extensive analysis in vitro (6,7,9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Cell types tested were: human hepatoma (HepG2), mammary carcinoma (MCF71, human mammary epithelium (HBLlOO), cervical carcinoma (HeLa), bladder carcinoma (T.241, fibrosarcoma (HT1080), epidermoid carcinoma (A431), choriocarcinoma (BeWo), rhabdomyosarcoma (RD), three strains of diploid human embryonic fibroblasts M38, MRC5 and IMRgO), two cultures of cells from human amniotic fluid, two lines of monkey kidney origin (BSC and CVl), and primary cultures of human embryonic kidney, human mammary carcinoma, adult human dermal fibroblasts, basal cell carcinoma and normal human epidermal cells. Many of these cell types are reported to synthesize fibronectin or laminin (Hynes and Yamada, 1982;Grotendorst et al, 1982;Yamada, 1983), and we have previously reported a number of these lines to exhibit a spreading response to SF and fibronectin (Barnes and Sato, 1979;198Ob;Barnes, 1982;Silnutzer and Barnes, 1985).…”
Section: Sf Synthesis By Hepg2 Cells In Culturementioning
confidence: 91%
“…4,5, Pate1 and Lodish, 19841, suggesting that the mechanism by which serum promotes HepG2 cell spreading in culture may be solely through the action of SF. Interestingly, although fibronectin does not promote HepG2 cell spreading, peptides derived from the proposed cell-binding site of fibronectin are capable of inhibiting SF-promoted spreading of HepG2 cells as well as other cell types (Silnutzer and Barnes, 1985).…”
Section: Sf Synthesis By Hepg2 Cells In Culturementioning
confidence: 99%
“…Synthetic peptides related to regions of attachment factors thought to interact with cells or fragments derived proteolytically from these factors are capable of inhibiting cell spreading on substratum-bound spreading factors if presented to cells in sufficient concentration in soluble form (16,18,20). Assays of this type are carried out by including the soluble peptides in the cell suspension that is plated on the precoated dish (step 4 of procedure A or step 3 of procedure C).…”
Section: IVmentioning
confidence: 99%